Activity of silver nanoparticles on prokaryotic cells and Bothrops jararacussu snake venom. (2nd January 2019) - Oliveira, Isadora Caruso Fontana; de Paula, Marina Oliveira; Lastra, Hellen Cristine Boschilha; Alves, Bruno de Brito; Moreno, Débora Antunes Neto; Yoshida, Edson Hideaki; Amaral Filho, Jorge; Cogo, José Carlos; Varanda, Eliana Aparecida; Rai, Mahendra; Santos, Carolina Alves dos; Oshima-Franco, Yoko
Abstract: Nanoparticle-conjugated venom-toxins of venomous animals and its therapeutic efficacy against emerging or neglecting diseases is a promising strategy. In this study, silver nanoparticles (AgNPs ∼50 nm, 0.081 mg mL −1 ) were studied against the neuromuscular blockade, myotoxic effects induced by Bothrops jararacussu venom (60 µg mL −1 ) and also against prokaryotic cells. The neurotoxicity was evaluated on ex vivo mouse phrenic nerve-diaphragm using traditional myographic technique, able to obtain functional contractile responses and to check the neurotransmission. The myotoxicity on mammalian cells was evaluated in muscles resulting from pharmacological assays using routine histological techniques and light microscopy. The toxicity to prokaryotic cells was evaluated on Salmonella typhimurium TA100 without metabolic activation. The in vitro preincubation model between AgNPs and venom was enough to abolish toxic effects of B. jararacussu venom, but mammalian cells were highly sensitive to AgNPs more than prokaryotic cells, by acting as dose-independently and dose-dependently parameters, respectively. These results allowed us to conclude that AgNPs showed promising activity as antivenom agent but for its safer use, the toxicity should be evaluated on experimental animals.